TAT modification facilitates nose-to-brain transport of intact mPEG-PDLLA micelles: Evidence from aggregation-caused quenching probes. (June 2020) - Ahmad, Ejaj; Lv, Yongjiu; Zhu, Quangang; Qi, Jianping; Dong, Xiaochun; Zhao, Weili; Chen, Zhongjian; Wu, Wei; Lu, Yi
Graphical abstract: Highlights: ACQ probes are crucial for tracking the intact micelles. Trigeminal nerve pathway is more feasible in nose-to-brain delivery of intact micelles than the olfactory route. TAT modification is crucial for intact micelles to permeate into the olfactory bulb from the nasal cavity. TAT modification improves the cellular uptake of the intact micelles. Cargos are mainly released from micelles and diffuse in molecular form into the brain. Abstract: Nanoparticles have been widely adopted in nasal drug delivery for the treatment of brain diseases. However, the feasibility of nose-to-brain transportation of intact nanoparticles and the possible corresponding pathways remain poorly understood. In this study, nose-to-brain delivery of mPEG-PDLLA micelles (PMs) and TAT functionalized ones (TAT-PMs) were explored by labeling with aggregation-caused quenching (ACQ) probes, which provide on-to-off fluorescent switching from loaded to released states for identification of the intact nanocarriers. Coumarin-6 was simultaneously loaded in the micelles to mimic cargos. Evidence of nose-to-brain translocation was collected through IVIS live imaging and ex vivo histological imaging. TAT modification reduced the retention of intact micelles in the nasal cavity due to the enhanced absorption and the subsequent distribution to other organs. Trigeminal nerve is the main transportation pathway for nose-to-brain delivery of the intact micelles. TAT modification improves the cellular uptake of the intact micelles and is crucial for micelles to permeate into the olfactory bulb. Nevertheless, cargos are mainly released from the micelles and diffuse into the brain. In conclusion, TAT modification facilitates nose-to-brain delivery of micelles, whereas cargos can be released and permeated into the brain in greater amounts.